aPDT for periodontitis treatment in ovariectomized rats under systemic nicotine - Garcia, Valdir Gouveia [UNESP] (2018)
Background: This study evaluated the antimicrobial photodynamic therapy (aPDT) as an adjunctive therapy to scaling and root planning (SRP) for the treatment of experimental periodontitis (EP) in ovariectomized rats under systemic nicotine. Methods: Female ovariectomized rats (n = 180) were divided into two groups: vehicle administration (Veh) and nicotine administration (Nic). Mini-pumps containing either vehicle or nicotine were inserted in the rats 30 days before the induction of EP, which was induced by placing a ligature around the left mandibular first molar. The rats were randomly divided into three treatment subgroups: SRP, SRP plus low-level laser therapy (LLLT), and SRP plus aPDT. aPDT consisted of the application of a phenothiazine photosensitizer followed by LLLT. Ten animals from each group were euthanized at days 7, 15, and 30 after periodontal treatment. The furcation region was evaluated using histological, histometric analyses and immunolabelling for PCNA, TRAP, RANKL, and OPG. Results: Nicotine administration resulted in greater bone loss (BL). aPDT resulted in lower BL compared to SRP. aPDT showed higher quantities of PCNA-positive cells compared to SRP, regardless of the nicotine status. aPDT resulted in less recruitment of osteoclasts and lower RANKL immunolabelling compared to LLLT and SRP. Conclusion: aPDT was effective in animals treated with nicotine.